Labour economics - Smith, Stephen W. (Stephen Walter), 1955- (Routledge, 2003)
Now in its 2nd edition this comprehensive and accessible text provides a detailed study of labour market issues. This excellent new book is a must-see for all those involved in Labour Economics.